SOCIO-CULTURAL CHALLENGES OF ENGLISH TEACHING IN REMOTE AREAS OF INDONESIA - Poedjiastutie, Dwi; Mayaputri, Velmi; Arifani, Yudhi (TEFLIN Journal, 2021)
The development of English language learning in any country is interdependent with its socio-cultural experiences. Learning is determined by the social, historical, economic, political, and cultural dimensions of its context. This study aims to explore the socio-cultural challenges of teaching English in a remote area. It was conducted in Pemana Island (East Nusa Tenggara) using the ethnography exploration. Pemana is one of the Indonesian government's target locations for a teaching program to improve educational quality and overcome the problem of limited number of teachers in remote areas. This program involves bachelor degree holders of English being deployed to teach in the frontier, outlying and underdeveloped region. Several challenges of English teaching and learning emerge due to socio-cultural aspects. These include the economic situation of the society, the community beliefs about English teaching, and the ill-fitting curriculum with the social condition. The teaching implications are then discussed here.